2017
DOI: 10.1073/pnas.1708240114
|View full text |Cite|
|
Sign up to set email alerts
|

Cdk5-dependent phosphorylation of liprinα1 mediates neuronal activity-dependent synapse development

Abstract: The experience-dependent modulation of brain circuitry depends on dynamic changes in synaptic connections that are guided by neuronal activity. In particular, postsynaptic maturation requires changes in dendritic spine morphology, the targeting of postsynaptic proteins, and the insertion of synaptic neurotransmitter receptors. Thus, it is critical to understand how neuronal activity controls postsynaptic maturation. Here we report that the scaffold protein liprinα1 and its phosphorylation by cyclin-dependent k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…To investigate the heritability pattern across large-scale brain functional networks, we clustered 97 brain regions into 18 functional communities (Buckner et al 2008;Sporns and Betzel 2016;Huang et al 2017) (Supplementary Table S6). We found that the heritability estimates vary substantially across these functional communities, while the degree of gene control on these functional communities is comparable (Fig.…”
Section: Heritability Pattern Across Brain Function Networkmentioning
confidence: 99%
“…To investigate the heritability pattern across large-scale brain functional networks, we clustered 97 brain regions into 18 functional communities (Buckner et al 2008;Sporns and Betzel 2016;Huang et al 2017) (Supplementary Table S6). We found that the heritability estimates vary substantially across these functional communities, while the degree of gene control on these functional communities is comparable (Fig.…”
Section: Heritability Pattern Across Brain Function Networkmentioning
confidence: 99%
“…While at first sight the overexpressed gene sets appear to represent separate biochemical pathways, a common denominator of the related functions may be a high capacity for neuroplastic change. Thus, the physiological functions of tau protein and its associated kinases have been implicated in cytoskeletal flexibility, dendritic spine formation, and also more functional aspects of synaptic plasticity such as long-term depression ( Kimura et al , 2014 ; Mita et al , 2016 ; Wang and Mandelkow, 2016 ; Huang et al , 2017 ). Tau function is physiologically regulated by its phosphorylation state, and even transient hyperphosphorylation of tau can be observed under specific physiological conditions, where it has been associated with adaptive neuroprotective changes of the synapse ( Arendt et al , 2003 ; Wang and Liu, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…The resolution of STORM images is also affected by low localization density, but we do not have any structure that is too sparse to affect the conclusions. Besides, we have a robust protocol for labeling and tested different structures and no such issues were found (Huang et al, 2017; Liu et al, 2017; Cheng et al, 2018; Mao et al, 2019). Moreover, we measured the density of localization in Figures 3A,E, 5A,I to be >18 counts/nm 2 at the least dense region, which means the average distance between adjacent localized sites is below 20 nm.…”
Section: Discussionmentioning
confidence: 99%